Cardiorespiratory Endurance among End Year Student of Faculty of Pharmacy in Jatinangor, Bandung - Hemavahthy Mani; Tri Damiati Pandji; Putri Teesa (Faculty of Medicine Universitas Padjadjaran, 2019)
Background: Physical fitness indicates the ability of an individual to perform daily physical activities with ease. The major component of physical fitness is the cardiorespiratory endurance, which is assessed through maximal oxygen consumption (VO2 max). A decrease in cardiorespiratory endurance can be associated with a sedentary lifestyle. This study was conducted to determine the cardiorespiratory endurance among young adults in Jatinangor, Bandung.Methods: This cross-sectional study had used total sampling method, conducted among end year student of Faculty of Pharmacy, Universitas Padjadjaran from October–November 2013. The inclusion criteria wasall end year students who had no health-related problems and the students had to agree to participate in the study. After obtaining written informed consent from the participants, Astrand-Rhyming Step Test was performed to measure the level of VO2max.Results: In total, 32 students were included of whom 14 students (43.7%) had an average level of VO2 max and 9 (28.2%) had just below average level. Chi-square test results showed that there was no significant relationship (p>0.05) between VO2 max level and gender, BMI level, and smoking habit, but showed a significant relationship (p< 0.05) with exercising habit.Conclusions: The majority of the participants had an average level of VO2 max. A significant relationship between the level of VO2 max and exercising habit, suggesting a regular exercise for a better lifestyle.